KETAHANAN PANGAN PROVINSI KALIMANTAN BARAT - Iwan Setiabudi; Marisi Aritonang; Shenny Oktoriana (Fakultas Pertanian Universitas Tanjungpura, 2021)
According to Law No. 7 of 1996 and the Indonesian Government Regulation No. 68 of 2002 concerning food, food security is defined as a condition the fulfillment of food for households that reflected: : (1) adequate food availability, both in quantity and quality; (2) secure; (3) evenly; and (4) affordable In an effort to reduce community dependence only on rice as a staple food the government designed a food diversification policy through Presidential Instruction No. 14/1974 concerning Efforts to Improve the People's Food Menu (UMPMR). Food diversification is the most appropriate solution in solving problems in food needs. This research is entitled to analyze the role of food diversification on food security in West Kalimantan Province. The data analysis tool used was Microsoft exel 2013 and SPSS with Rank Spearman rho correlation. Based on the results and discussion in case studies the role of food diversification on the level of food security. West Kalimantan province is at a very low level. This is due to the high consumption of people in districts / cities in West Kalimantan Province for rice compared to other food consumption.Keyword : food security, food diversification, food consumtion.